Development Strategies for Small Culinary Businesses: A Case Study of Kopi Kesayangan in Medan City - Habib, Fauzan; Qarni, Waizul; Daulay, Aqwar Naser (Ilomata International Journal of Management, 2025)
This research aims to explore the development strategies carried out by small businesses at Kopi Kesayangan. To attract potential consumers by using intensive marketing strategies and prioritizing product identity and taste quality so that the public better knows them. A qualitative approach was used through data collection using literature studies, observations, and interviews. The research data analysis technique uses Ansoff Matrix analysis in development strategies to increase company income and attract potential new consumers. Kopi Kesayangan provides innovative tea variant products such as Thai tea. It also develops markets other than the campus area. It has outlets with their characteristics, with different characteristics being an attraction so that potential consumers are interested in buying and maintaining product quality to retain existing consumers.